"Mów! Ja każę." Słowo poetyckie jako narzędzie dialogu w cyklu "Sonety - zarysy" Karola Wojtyły = "Speak! I order you." Poetic word as the instrument of dialogue in the cycle "Sonety - zarysy" by Karol Wojtyła - Banaszak, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the cycle of Sonnets, included in the Renaissance Psalter, the function of the poetic word as the basis of multi-dimensional dialogue is markedly dominant. In this article, the author attempts to trace the dimensions of this dialogue. Talk, question, comment - usually particular, individual, specific, but still maintaining its universal character - is an essence of these poems, each of which contains at least one apostrophe, determining the perspective of communication.
Keywords: Jan Paweł II, papież (1929-2005); poezja polska - 20 w.; poezja religijna